Microstructural and mechanical properties degradation of the acceleration/deceleration zones in stainless steel 316L fabricated by selective laser melting - Won-Sang Shin; Taehyun Lee; Hyonkee Sohn; Yoon-Jun Kim; Changkyoo Park (Journal of Materials Research and Technology)
Additive manufacturing, particularly the selective laser melting (SLM) process, has emerged as an innovative technique for manufacturing complex geometries with precise control over phase composition and element distribution. However, the SLM process faces inherent challenges, such as a non-uniform microstructure and high residual stress in acceleration and deceleration scan (Ac/Dec) zones owing to the use of a galvanometer scanner. This study investigates the microstructural evolution within the Ac/Dec zones of selective laser-melted stainless steel 316L. A detailed analysis reveals that these zones exhibit unique microstructures, including random sub-grain sizes, σ phase formation, and multiple defects, differing from constant speed scan (CSS) zones. These variations occur because the laser energy input varies with the laser beam scan speed. A post-heat treatment at 1373 K relieves the residual stresses in the Ac/Dec zones, which results in the formation of annealing twins. However, these microstructural differences render it difficult to maintain uniform material properties and product quality, particularly in small-scale applications. The findings of this study show that the Ac/Dec zones exhibit distinct microstructures compared to the CSS zones. Addressing these differences can significantly enhance the performance and reliability of SLM products.